Chinese Plan of the Economic Belt of the Great Silk Road, SCO an the EAEU - T. Bordachev (Международная аналитика, 2015)
The paper deals with problems of interaction and mutual development of states within international organizations and economic-political strategic projects existing in Central Euarasia.